2016
DOI: 10.4103/0972-5229.186226
|View full text |Cite
|
Sign up to set email alerts
|

The role of C-reactive protein as a diagnostic predictor of sepsis in a multidisciplinary Intensive Care Unit of a tertiary care center in Nepal

Abstract: Aim:C-reactive protein (CRP) is a commonly used biomarker of sepsis, the leading cause of mortality in Intensive Care Units (ICUs). However, sufficient data are still lacking to strongly recommend it in clinical practice. The present study is aimed to find out its reliability in diagnosing sepsis.Materials and Methods:CRP was measured in ICU-admitted patients with systemic inflammatory response syndrome and compared using a cutoff of 50 mg/L with the gold standard for diagnosing sepsis, taken as isolation of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 13 publications
1
39
1
1
Order By: Relevance
“…The role of CRP in sepsis has been reported in multidisciplinary studies on patients in the ICU setting (34,35). The present study reported that the serum levels of HMGB1 and CRP were significantly increased in sepsis patients compared with those in healthy individuals.…”
Section: Discussionsupporting
confidence: 66%
“…The role of CRP in sepsis has been reported in multidisciplinary studies on patients in the ICU setting (34,35). The present study reported that the serum levels of HMGB1 and CRP were significantly increased in sepsis patients compared with those in healthy individuals.…”
Section: Discussionsupporting
confidence: 66%
“…Pradhan et al emphasised that CRP is useful in identifying patients with sepsis diagnosed with SIRS. In addition, they stated that CRP could be a very useful marker in resourcerestricted areas where sepsis specialists are not available and especially in places where data on procalcitonin or interleukins are not accessible [33]. In our study, although there was no difference between mortal and nonmortal cases diagnosed with sepsis, this does not minimise the fact that CRP may be beneficial in the diagnosis of sepsis, although it is not predictive for all aspects of the condition.…”
Section: Discussioncontrasting
confidence: 53%
“…Interleukin-6 (IL-6) and its downstream product, CRP, are therefore both well-known inflammatory molecules. Importantly, due to an increase in IL-6, circulaitng CRP levels can increase up to 1000 times during disease or inflammation [25]. We also included analysis of levels of HbA1c and lipid profiles, as these are markers that can confirm hyperglycemia and systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%